Time and Frequency Synchronization for OTFS - Bayat, Mohsen; Farhang, Arman (My University, 2022)
In this letter, we propose timing offset (TO) and carrier frequency offset (CFO) estimators for orthogonal time frequency space modulation (OTFS). The proposed estimators do not require any additional training overheads as they deploy the same pilot signal that is used for channel estimation. Hence, no additional training overhead is required for synchronization, thanks to the periodic properties of the pilot signal in the delay- time domain. Our proposed TO estimator finds the start of each OTFS block by searching for a periodic sequence in delay and time dimensions. The CFO is then estimated by finding the mean of the angles of a two-dimensional correlation function at the best timing instant. As a novel aspect of these estimators, the multipath diversity of the channel is exploited to achieve a high estimation accuracy. Finally, we show the efficacy of our proposed synchronization techniques through extensive simulations.
PUBLISHED
Keywords: OTFS, synchronization, timing offset estimation, carrier frequency offset estimation; Telecommunications; DIGITAL SIGNAL PROCESSING; ELECTRONICS; Signal Processing